Climate change, agriculture, and adaptation options for Honduras - Sanders, Arie; Thomas, Timothy S.; Rios, Ana R.; Dunston, Shahnila (International Food Policy Research Institute, 2019)
We use both biophysical and bioeconomic models to assess the impact of climate change on Honduran agriculture out to 2050. We find that for some key crops, such as maize and sugarcane, yield reductions will likely be larger in Honduras than most of the rest of the world will experience. We argue that the highest-value crop for Honduras—coffee—may also be the hardest hit by climate change. Maize is projected to have a productivity loss of around 12 percent as a direct result of climate change, but because of increased prices from climate change, yields are projected to only decline by 9 percent, as farmers will invest more in productivity. Beans are projected to lose 10 percent in yield, even after adjusting for the increased investment in productivity by farmers. Livestock may also experience productivity shocks due to climate change, particularly in the southern part of the country. We make recommendations to policy makers to enact appropriate policies to help farmers adapt to the various productivity losses that would otherwise be experienced because of climate change.